Szanse i zagrożenia funkcjonowania spółdzielni "Samopomoc Chłopska" związane z akcesją Polski do Unii Europejskiej - Grzegorzewski, Piotr (Chances and Threats of the "Samopomoc Chłopska" Co-Operatives Connected with Integration of Poland with the European Union, 2005)
This article includes the presentation of the results of empirical research which was conducted among managers of "Samopomoc Chłopska" co-operatives and concerned opinions about the ever more discussed and ever more up to date issue, namely - the integration of Poland with the European Union. Of all the important and dire problems connected with the ever closer process of integration the co-operatives are bothered by. The research concerned only the empirical material including the opinions of the surveyed people, which dealt with their hopes and fears connected with the integration of Poland with the European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 291-298